The Influence of Emotional Intelligence, Nurse Loyalty, Leadership Style, Intervention of Motivational Variables in Hospital - Sarah Ainar Rahman; Supriyantoro Supriyantoro; Rina Anindita (Syntax Corporation Indonesia, 2023)
Employees are human resources which are the most important assets to provide excellence to drive the dynamics of an organization or company. Loyal employees can be a very valuable asset for the organization because they can help get as much profit as possible for the organization. The purpose of this study was to analyze the influence of leadership, Emotion intelligence on employee loyalty with motivation as an intervening variable on nurses at the South Sumatra Type C Hospital. This research is a quantitative research, data collection was carried out using a questionnaire instrument. The number of samples determined is 120 employees. The sampling technique was done by purposive sampling. The analytical method using the partial least squares approach - structural equation modeling (SEM-PLS) with the SMART PLS program was used for data analysis. The results showed that leadership style had a positive and significant effect on employee motivation and loyalty, Emotion intelligence had a positive and significant effect on employee motivation and loyalty, and work motivation had a positive and significant effect on employee loyalty at the South Sumatra Type C Hospital.